Dopant induced effect on electrocatalytic reduction of nitrobenzene using conducting polypyrrole thin film electrodes - Adhikari, Arindam; Radhakrishnan, S. (Journal of Applied Polymer Science, 2011)
Conducting polypyrrole electrodes were prepared by electrochemical polymerization of pyrrole on vacuum-metallized glass substrates. These electrodes were modified by doping with a range of metal halides as dopant ions having different electronegativity. Electrochemical reduction of nitrobenzene using these electrodes was studied by means of cyclic voltammetry technique in acetonitrile medium containing aqueous HClO(4) (0.1M) as supporting electrolyte. It was found that the electronegativity of the dopant ion played a very important role in the electrocatalytic activity. Polypyrrole doped with nickel chloride gave the highest anodic current at the reduction potential of nitrobenzene. The results were explained on the basis of charge transfer efficiency at the electrode-electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 719-724, 2011
Keywords: charge transfer; conducting polymer; Doping; electrocatalysis; nitrobenzene; polypyrrole; reduction